Ekstrakulikuler Art Painting dalam Meningkatkan Kreativitas Siswa pada Kompetensi Pembelajaran Abad 21 di Sekolah Dasar - Muhammad Maskur Musa; Rahmat Kamal (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The era of globalization has recently begun to have an impact on the lives of Indonesian people. This era of globalization is indicated by the widespread development of technology and information, which results in changes in one's life in all fields. Including changes to culture, these changes are shown by their impact on the culture of Indonesian society. Now, Indonesians prefer western culture over the original Indonesian culture, including art. The purpose of this study is to explain the role of the art painting extracurricular in increasing the creativity of high-level students in the 21st century learning competencies in elementary schools. Field research with a qualitative descriptive approach was used in this study.In this study, data was collected using several techniques, including observation, interviews, and documentation. The results of this study explain that the art painting extracurricular at Candi Areng Elementary School is attended by high-level students, namely grades 4-6. This extracurricular is held once a week on Monday at 12.00-14.00 after students carry out the learning process. The art painting extracurricular at Candi Areng Elementary School itself is in great demand by the students. The interest of these students is shown by the number of students who take part in the training. The art painting extracurricular at Candi Areng Elementary School is carried out in several steps. With the steps taken by high-level students, students are required to think more, and with students' thinking, creativity emerges in them. Creativity is a very important competency in the 21st century, because this is a competency that can make students more creative about everything they find.